Hydrological and pedological consequences in the changes in forest areas - Ferreira, Antônio José Dinis (1998)
The expansion of afforestation produces a change at ecosystems in general, and on natural resources sustainability in particular. Results on the pine and eucaliptos forests implications are presented, namely on water resources, which include hydrological and hydrochemical processes. Erosion rates are presented for the different forest land uses. A particular attention is given to two of the most catastrophic events that occur in the portuguese forest: forest fires and rip-ploughing following the highest slope angle.